The effect of teaching Latin on the education system in Lithuania during the Soviet period - Brunevičiūtė, Raimonda (Literatūra, 2009)
The discussion on teaching Latin under the Soviet occupation is important for several reasons: first, researchers who analyzed education of the period 1940–1990 focused on the other issues of education, leaving issues of teaching Latin virtually unexplored; second, the Soviet education system was formally based neither on the classical nor the modern concept of education. Investigation of the purpose of teaching Latin in the Soviet system of education reveals to which extent education in Lithuania remained distinctive and preserved the continuity of the classical system. Analysis has shown that the classical foundations of humanitarian education, realized through teaching Latin, were fragmented and inconsistent. During the Soviet occupation, the Latin language had a very important effect on helping to preserve the elements of classical education in Lithuania.